Perjanjian Baku dalam Dunia Bisnis dikaitkan dengan Hak Asasi Manusia - Novenanty, Wurianalya Maria (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2017)
In business activities, there is a known type of agreement termed as “standard agreement”. This standard agreement is an agreement which is made by only one of the parties involved, and the counterparty is not in the position to bargain with regards to the content of the agreement. The counterparty solely accepts the predetermined terms and conditions in such agreement. Here this kind of agreement indicates that there is inequality of positions between the parties, which is contrary to the principle that “all human beings are equal”, the fundamental principle as the source of human rights. Human rights are carried by each person since birth, and such basic rights are equally owned and must be respected by others. However, in business contexts, efectivity and efficiency are highly considered in running the businesses, and human rights tend to be ignored whether undeliberately or deliberately. This article finds it imperative to analyse the standard agreement in Indonesia in the light of civil law and human rights law. The resulting contracts should contain the distribution of rights and obligations between the parties involved. And to produce a proper contract, business executives are the first to get a complete understanding of how to make their business in accordance with human rights.